Sustainability Challenges of Multiple-Use Water Systems in Khatyad Rural Municipality, Nepal - Rimal, Raghunath; Goshain, Raj (Yayasan Sembilan Pemuda Indonesia, 2025)
This study investigates the sustainability challenges of Multiple-Use Water Systems (MUS) in rural hilly areas, focusing on identifying key problems, their causes, effects, and potential solutions to enhance long-term system viability. A mixed-methods approach was employed, including field observations, interviews, focus group discussions, and a questionnaire survey of 157 purposively selected respondents. Data were analyzed using the Relative Importance Index (RII) based on a 5-point Likert Scale to prioritize issues and solutions. Major sustainability challenges include poor fund management, limited technical knowledge, inadequate maintenance, lack of insurance practices, and weak monitoring. Root causes were identified as irregular Water User Group (WUG) meetings, inconsistent tariff collection, insufficient training, and lack of technical support. The study highlights the need for capacity-building, regular maintenance, formal scheme registration, and stronger government coordination to improve MUS sustainability. This study provides a systematic assessment of MUS sustainability issues using participatory methods and quantitative prioritization, offering new insights into the socio-technical barriers affecting community-managed water systems in hilly regions. To ensure MUS sustainability, policymakers and practitioners should focus on institutional strengthening, financial management training, and improved technical support for WUGs. Regular monitoring, insurance mechanisms, and government collaboration are also critical for long-term success. The research contributes to the discourse on sustainable rural water management by empirically identifying key challenges and actionable solutions for MUS, demonstrating their potential to enhance food security and reduce poverty in vulnerable communities if properly managed.